Colonial legacy and the nature of democracy in Southeast Asia : a comparative study of Malaysia and Indonesia - Fairuz Hidayat Merican Bin Wan Merican (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2006)
Colonialism and democracy are often discussed separately. This is probably due to the fact that they seem to contradict one another. In addition, nations that were once under colonial rule often neglect that particular part of their history since their focus now is towards establishing and consolidating democracy. However, colonial experience may not only remain a part of a nation’s past, it may also influence a nation’s future whether it chooses the path of democracy or not. However, there is a possibility that the nations we see today have been shaped in part by their colonial experience. One such example is Southeast Asia. This thesis intends to do a comparative study on the relationship between the colonial experience of Southeast Asian nations and their nature of democracy. The thesis focuses on two countries – Malaysia and Indonesia. This thesis will be useful to ascertain whether or not their road towards democracy has been influenced by elements of their colonial legacy. The method of data collection used in this thesis is documentary research. Information from books, journals and websites pertaining to the colonial history of Malaysia and Indonesia, the method in which both countries achieved independence as well as the various aspects of their experience with democracy are the source of data for this thesis. Although there are differences in the colonial legacy and method of gaining independence in Malaysia and Indonesia, they do not greatly affect the differences in the nature of democracy in both countries. The favourable colonial policies of the British and the peaceful transition to independence helped Malaysia achieve a relatively more conducive nature of democracy. Nevertheless, as Indonesia continued to grow as an independent nation, its nature of democracy experienced various changes and currently experiences a comparatively better nature of democracy despite its colonial legacy.